Issues Concerning the Homeopathic Education Sector: A Professional Viewpoint (Homoeopathy for All, 2025)
Homeopathy, a widely practiced  alternative system of medicine,  occupies a significant position in  India’s healthcare and educational  framework governed by the National  Commission for Homoeopathy  (NCH) under the Ministry of  AYUSH. However, the homeopathic  education sector faces persistent  systemic challenges that undermine  its quality, credibility, and potential  for global integration. This article  explores the major issues affecting  homeopathic education from an  expert standpoint. Addressing  these multifaceted challenges is  crucial to enhance the credibility,  relevance, and future sustainability  of homeopathic education in India. Homeopathy, developed  in the late 18th century by Dr.  Samuel Hahnemann, has evolved  significantly in India. Governed  today by the National Commission  for Homoeopathy (NCH) under  the Ministry of AYUSH, it boasts  a structured system of education  with undergraduate (BHMS) and  postgraduate (MD Hom) programs. Despite structured curricula and  institutional oversight, critical  issues persist, particularly in  infrastructure, faculty standards,  patient inflow, research integration,  and employability. These issues not  only affect the quality of education  but also diminish the credibility  of homeopathy as a scientific  discipline.
Keywords: employability; Inadequate Infrastructure; exposure; Underrepresentation